2018
DOI: 10.1155/2018/9263296
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Moisture-Holding Capacity with Support Vector Machines in Dry Subhumid Tropics

Abstract: Soil moisture-holding capacity data are required in modelling agrohydrological functions of dry subhumid environments for sustainable crop yields. However, they are hardly sufficient and costly to measure. Mathematical models called pedotransfer functions (PTFs) that use soil physicochemical properties as inputs to estimate soil moisture-holding capacity are an attractive alternative but limited by specificity to pedoenvironments and regression methods. This study explored the support vector machines method in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 45 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Several studies have used KNN type of ML to predict soil hydraulic properties (e.g., Botula et al, 2013;Nemes et al, 2006Nemes et al, , 2008; Elshorbagy et al (2010) identify KNN as an attractive modeling technique for hydrology applications. Many studies have used SVR algorithm to model soil hydraulic properties (e.g., Angelaki et al, 2018;Kaingo et al, 2018;Kotlar et al, 2019;Mady & Shein, 2018;Singh et al, 2019). Recently, some studies have found that SVR models predicted soil hydraulic properties more accurately than artificial neural network models (Khlosi et al, 2016;Twarakavi et al, 2009;Zhang et al, 2018).…”
Section: Algorithmsmentioning
confidence: 99%
“…Several studies have used KNN type of ML to predict soil hydraulic properties (e.g., Botula et al, 2013;Nemes et al, 2006Nemes et al, , 2008; Elshorbagy et al (2010) identify KNN as an attractive modeling technique for hydrology applications. Many studies have used SVR algorithm to model soil hydraulic properties (e.g., Angelaki et al, 2018;Kaingo et al, 2018;Kotlar et al, 2019;Mady & Shein, 2018;Singh et al, 2019). Recently, some studies have found that SVR models predicted soil hydraulic properties more accurately than artificial neural network models (Khlosi et al, 2016;Twarakavi et al, 2009;Zhang et al, 2018).…”
Section: Algorithmsmentioning
confidence: 99%
“…Although the SVR algorithm has many hyperparameters, in this study, we chose four hyperparameters (C, ε, γ and the kernel function) that were tuned using the GridSearchCV module. According to Kaingo et al [63], a successful SVR implementation depends on selecting a suitable kernel function, choice of the cost parameter C, and the "tube" insensitive variable ε. The "RBF" (radial basis function) performed better than the linear and sigmoid functions.…”
Section: Model Performance Assessmentmentioning
confidence: 99%
“…Therefore, the existing PTFs developed internationally still need to be calibrated and validated locally against measurements before they can be reliably used to estimate hydraulic properties in new sites that are located in different regions from their origins [12,[44][45][46]. However, the lack of representative information on soil hydraulic properties hinders the validation of the existing PTFs and the development of local PTFs in many countries of the world [12,24,46,47]. Consequently, the existing PTFs are often applied without any calibration or validation in many regions as the result of data constraints [13,46,48].…”
Section: Introductionmentioning
confidence: 99%